Hypoxia increases susceptibility of human intestinal epithelial cells to rotavirus infection through repression of interferon induction - Jacobs, Sorin; Münchau, Stephanie; Uckeley, Zina M.; Passarelli, Gianna V.; David, Asher; Briggs, Skyler; Burke, James M.; Stanifer, Megan L.; Boulant, Steeve (Gut microbes, 2025)
Intestinal epithelial cells (IECs) serve as both a physical barrier and a source of robust antiviral interferon (IFN) response. As such, they constitute the primary barrier that enteric viruses, such as rotavirus, need to overcome to initiate infection. The gut is characterized by very low oxygen levels (hypoxia) within the lumen, resulting in a unique hypoxic physiological environment in which rotavirus infection occurs. Depending on the tissues or viruses, conflicting results have been described for the role of hypoxia in regulating viral infections, where hypoxia could have either a proviral or antiviral function. Since intestinal epithelial cells naturally exist in a hypoxic environment, it is essential to investigate how these conditions affect rotavirus infection. We found that hypoxia promotes rotavirus infection, resulting in increased virus replication and production of infectious virus particles. We showed that this increased production of rotavirus particles under hypoxia is due to a decreased induction of IFNs, leading to a decreased expression of IFN stimulated genes and antiviral protection. RNA sequencing showed a robust decrease in ISG production in hypoxia for both rotavirus infection and poly I:C transfection, suggesting a conserved inhibition of IECs’ IFN response to viral pathogen challenges under hypoxic conditions. Functional analyses revealed that hypoxia impairs signal transduction leading to IFN expression by negatively regulating the activation of the master signaling molecule TBK1. Mechanistically, we determined that hypoxia induces the expression of the protein phosphatase PP2A which is responsible for the hypoxia-induced impairment of TBK1 activation. Importantly, we confirmed that this hypoxia-mediated dampening of immune response was not restricted to rotavirus infection but dampened the IFN induction of a broad range of viruses and immune stimuli. Together, we propose that hypoxia creates an immune-suppressive environment through downregulation of IFN, representing a novel proviral mechanism for hypoxia in the human gastro-intestinal tract.